THE RISE AND DEVELOPMENT OF THE AMERICAN BIOGRAPHICAL NOVEL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The biographical novel, being a phenomenon of the XX century, has already gained its own fame among the readers and the canons of its creations have been worked out by many American writers and critics. Once as the description of the lives of religious figures in the form of hagiographies, the modern biographical novel is a piece of writing about strong individuals whose deeds changed the society and course of history. As biography is greatly connected with history, the genre – biographical novel in American literature emerged as the consequence of great changes in American history of XIX century. Many political figures, leaders of opposition and abolitionists became the subjects of the biography. At the same time, the first feministic approach to the novels can be also observed within this period. This work aims to demonstrate the diachronic observation of the development of the biographical novel as a genre, and to provide the overview of the most outstanding biographers of the United States and their works.